Phosphoglycerate mutase 2 is elevated in serum of patients with heart failure and correlates with the disease severity and patient’s prognosis - Li Min (De Gruyter, 2021)
Heart failure (HF) is a serious and advanced stage of various cardiac diseases with high mortality and rehospitalization rates. Phosphoglycerate mutase 2 (PGAM2) overexpression was identified in the serum of patients with HF.